The contribution of Orenburg scholars and educators to the development of a system for preparing students for a conscious choice of teaching profession in the late soviet period - Svetlana A. Alyoshina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The relevance of the research is due to the dynamically increasing need of schools for teaching staff. Today, such a socio-pedagogical phenomenon as "psychological and pedagogical classes" is being revived. Orenburg State Pedagogical University has extensive experience in the theory and practice of introducing new forms of vocational guidance for schoolchildren to the teaching profession, including the organization of psychological and pedagogical classes. The purpose of the research is to reconstruct the process of vocational guidance of adolescents and high school students for teaching professions in Orenburg region in the late Soviet period. The choice of research methods is determined by the peculiarities of historical and pedagogical knowledge. The methods of scientific research were: theoretical analysis of normative documents, study of primary sources, comparative historical method, method of reconstruction, systematic analysis of psychological and pedagogical literature on the problem of research, generalization of theoretical and practical data. Theoretical significance the research consists of defining the theory and practice of career guidance for schoolchildren in the teaching profession in the 70–80s of the 20th century.